Combination of gradual and rapid weight loss: Effects on physical performance and psychological state of elite judo athletes - Koral, J.; Dosseville, F. (Journal of Sports Sciences, 2009)
The aim of the present study was to examine the effects of a combination of gradual and rapid body mass loss on the physical performance and psychological state of elite judo athletes. Participants were divided into two groups: the experimental (diet) group needed to reduce body mass by 2-6%, whereas the control group did not need to lose body mass. Body mass, percentage of body fat, vertical jump, repetitions of judo movements, rowing with additional loads, and the Profile of Mood States were assessed at 4 weeks before a championship and again one day before the same championship. Compared with 4 weeks before the championship, the experimental group showed a significant decrease in body mass (-4 ± 1.1%, P < 0.05), estimated body fat (-10 ± 4.0%, P < 0.05), and judo movement repetitions over 30 s (-4.5 ± 2.7, P < 0.05), and an increase in scores for confusion (-14.6 ± 7.9, P < 0.05) and tension (-10.1 ± 12.5, P < 0.05), but a decrease in vigour (11.3 ± 8.5, P < 0.05), one day before the championship. There was no difference in squat jump or countermovement jump performance or in judo movement repetitions over 5 s. Our results show that for the experimental group some aspects of performance were impaired one day before a competition, but performance of judo movements over 5 s was not affected.